Atributos qualitativos e funcionais do camu-camu e elaboração de produtos com potencial funcional - Grigio, Maria Luiza (2017)
To meet the new market requirements and boost the consumption of camu-camu fruit and its derivatives, the understanding of its functional potential is necessary, which can be performed by comparing camu-camu with other fruits that are frequently consumed. The creation of new formulations of popsicles and jam that may encourage and enhance consumption is a potential strategy that exploits the nutritional richness of the species. Thus, the determination of the chemical and physical-chemical properties of the fruits and products formulated with camu-camu may contribute to increase the demand of the consumer market. In this sense, the objective of this work was to characterize the different parts of camu-camu fruit; to compare camu-camu with other fruits; and to formulate camu-camu popsicles and jam. Products were characterized to verify the maintenance of the bioactive compounds, aiming at products with high nutritional and functional potential. To this end, four experiments were carried out: I- Qualitative evaluation and biocompounds present in different parts of camu-camu fruits; II- Evaluation of the qualitative and functional properties of camu-camu and ten other fruits; III- Sensory evaluation, characterization and nutraceutical potential of camu-camu jam alone and mixed with other fruits; And IV- Sensorial, qualitative and functional evaluation of different formulations of camu-camu popsicles. Results show the great potential of camu-camu fruit as source of vitamin C and other phenolic compounds, being considered a good source of antioxidants. It is well known that the products developed from camu-camu also have great antioxidant potential and can be exploited and consumed as functional foods.